Upregulation of PD‐L1 by SARS‐CoV‐2 promotes immune evasion. Issue 2 (17th January 2023) - Huang, Hsiang‐Chi; Wang, Shih‐Han; Fang, Guo‐Chen; Chou, Wen‐Cheng; Liao, Chun‐Che; Sun, Cheng‐Pu; Jan, Jia‐Tsrong; Ma, Hsiu‐Hua; Ko, Hui‐Ying; Ko, Yi‐An; Chiang, Ming‐Tsai; Liang, Jian‐Jong; et al.
Abstract: Patients with severe COVID‐19 often suffer from lymphopenia, which is linked to T‐cell sequestration, cytokine storm, and mortality. However, it remains largely unknown how severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) induces lymphopenia. Here, we studied the transcriptomic profile and epigenomic alterations involved in cytokine production by SARS‐CoV‐2‐infected cells. We adopted a reverse time‐order gene coexpression network approach to analyze time‐series RNA‐sequencing data, revealing epigenetic modifications at the late stage of viral egress. Furthermore, we identified SARS‐CoV‐2‐activated nuclear factor‐κB (NF‐κB) and interferon regulatory factor 1 (IRF1) pathways contributing to viral infection and COVID‐19 severity through epigenetic analysis of H3K4me3 chromatin immunoprecipitation sequencing. Cross‐referencing our transcriptomic and epigenomic data sets revealed that coupling NF‐κB and IRF1 pathways mediate programmed death ligand‐1 (PD‐L1) immunosuppressive programs. Interestingly, we observed higher PD‐L1 expression in Omicron‐infected cells than SARS‐CoV‐2 infected cells. Blocking PD‐L1 at an early stage of virally‐infected AAV‐hACE2 mice significantly recovered lymphocyte counts and lowered inflammatory cytokine levels. Our findings indicate that targeting the SARS‐CoV‐2‐mediated NF‐κB and IRF1‐PD‐L1 axis may represent an alternative strategy to reduce COVID‐19 severity.